Sistem Informasi Inventory Berbasis Website Menggunakan Metode Waterfall - Harits, Dalhats Abiyyu Idzal; Anshor, Abdul Halim; Tedi, Nanang (Journal of Information System Research (JOSH), 2024)
As information technology develops today, the use of computers has become a very good alternative way for information needs and is the right solution for managing data compared to information carried out manually. However, Cahaya Bangun Utama Building Store still uses manual recording of goods, which results in problems such as recording warehouse stock which still uses traditional methods such as recording the incoming and outgoing goods using a notebook, making it easy for errors to occur when managing a building shop. The method used in this research is the Waterfall method, and will be built using the PHP programming language, the XAMPP framework, and a MySQL database. The aim of this research is to create a website-based inventory information system that will help building stores and increase the efficiency of recording warehouse stock. The results of this research show that Cahaya Bangun Utama Building Store can manage warehouse stock more effectively and efficiently.